A Quantitative Evaluation of Medication Histories and Reconciliation by Discipline - Kramer, Joan S. (Hosp Pharm, 2014)
BACKGROUND/OBJECTIVE: Medication reconciliation at transitions of care decreases medication errors, hospitalizations, and adverse drug events. We compared inpatient medication histories and reconciliation across disciplines and evaluated the nature of discrepancies. METHODS: We conducted a prospective cohort study of patients admitted from the emergency department at our 760-bed hospital. Eligible patients had their medication histories conducted and reconciled in order by the admitting nurse (RN), certified pharmacy technician (CPhT), and pharmacist (RPh). Discharge medication reconciliation was not altered. Admission and discharge discrepancies were categorized by discipline, error type, and drug class and were assigned a criticality index score. A discrepancy rating system systematically measured discrepancies. RESULTS: Of 175 consented patients, 153 were evaluated. Total admission and discharge discrepancies were 1,461 and 369, respectively. The average number of medications per participant at admission was 8.59 (1,314) with 9.41 (1,374) at discharge. Most discrepancies were committed by RNs: 53.2% (777) at admission and 56.1% (207) at discharge. The majority were omitted or incorrect. RNs had significantly higher admission discrepancy rates per medication (0.59) compared with CPhTs (0.36) and RPhs (0.16) (P < .001). RPhs corrected significantly more discrepancies per participant than RNs (6.39 vs 0.48; P < .001); average criticality index reduction was 79.0%. Estimated prevented adverse drug events (pADEs) cost savings were $589,744. CONCLUSIONS: RPhs committed the fewest discrepancies compared with RNs and CPhTs, resulting in more accurate medication histories and reconciliation. RPh involvement also prevented the greatest number of medication errors, contributing to considerable pADE-related cost savings.